Coupling between perception and action timing during sensorimotor synchronization - Serrien, Deborah J.; Spapé, Michiel M. (Elsevier, 2010)
Time is an important parameter in behaviour, especially when synchronization with external events is required. To evaluate the nature of the association between perception and action timing, this study introduced pitch accented tones during performance of a sensorimotor tapping task. Furthermore, regularity of the pacing cues was modified by small (subliminal) or large (conscious) timing perturbations. A global analysis across the intervals showed that repeated accented tones increased the tap-tone asynchrony in the regular (control) and irregular (subliminal) trials but not in the irregular trials with awareness of the perturbations. Asynchrony variability demonstrated no effect of accentuation in the regular and subliminal irregular trials, whereas it increased in the conscious irregular trials. A local analysis of the intervals showed that pitch accentuation lengthened the duration of the tapping responses, but only in the irregular trials with large timing perturbations. These data underline that common timing processes are automatically engaged for perception and action, although this arrangement can be overturned by cognitive intervention. Overall, the findings highlight a flexible association between perception and action timing within a functional information processing framework.